Phytodiversity and Ecological Aspects Evaluation of Moist Temperate Himalayan Belt, Azad Jammu and Kashmir. - Sajid Safeer (Bulgarian Journal of Soil Science, 2019)
To access floristic composition and ecological characteristics, present study was carried out in moist temperate territories of district Bagh. The altitude of the study area varies between 1500 m and 3500 m. Vegetation of the area was mostly therophytic, hemicryptophytic, nanophanerophytic, nanophyllus and microphyllus. Based on IVI twelve plant stands were recognized and all of them were found to be heterogeneous. Environmental factors such as climate, soil condition etc. were studied in relation to vegetation structure. The soil of investigated area varied from heavy loam to clay and clay loam with pH of 5.83 - 7.31 while saturation% age differed from 43 – 62%. Electrical conductivity ranged from 0.8 - 0.21 ds/m, organic matter% age from 3.3 - 6.2, phosphorus from 9 - 21 ppm and potassium from 240 - 412 ppm. The highest recorded Simpson Diversity Index value was 15.67 while lowest was 6.30, species richness was high at an altitude of 2520 m i.e. 1.11 while lowest at 1926 m which was 0.71. Maturity index value lies in between 40.5 - 60.7 while equitability values ranged from 0.66 to 1.63. The present research would serve as baseline information for the future researchers in related fields